Analisis Rencana Detail Tata Ruang dan Strategi Pengembangan Kawasan Kabupaten Administrasi Kepulauan Seribu - Ramones (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2025)
The Detailed Spatial Plan (RDTR) of the Administrative Regency of the Kepulauan Seribu is a crucial instrument in supporting sustainable and adaptive coastal development. This region possesses unique geographical characteristics that require a spatial planning approach based on local ecosystem, social, and economic conditions. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the implementation of the RDTR of the Kepulauan Seribu, as well as provide strategic recommendations for regional development. The method used is a literature study with a descriptive-analytical approach based on secondary data. The analysis results show that the main strength of the region lies in its extensive tourism and conservation areas, while its primary weakness is the limited basic infrastructure and spatial data management. Significant opportunities arise from the growing trend of ecotourism and strong government policy support, yet the region also faces serious threats such as natural disasters and conflicts over spatial use. This study recommends the integration of technology, human resource development, and improved spatial governance as strategic steps toward achieving inclusive and sustainable spatial planning in the Kepulauan Seribu. Rencana Detail Tata Ruang (RDTR) Kabupaten Administrasi Kepulauan Seribu merupakan instrumen penting dalam mendukung pembangunan wilayah pesisir yang berkelanjutan dan adaptif. Wilayah ini memiliki karakteristik geografis unik yang menuntut pendekatan perencanaan ruang berbasis ekosistem, sosial, dan ekonomi lokal. Penelitian ini bertujuan untuk menganalisis kekuatan, kelemahan, peluang, dan ancaman (SWOT) dalam implementasi RDTR Kepulauan Seribu serta rekomendasi strategi dalam pengembangan kawasan. Metode yang digunakan adalah studi literatur dengan pendekatan deskriptif analitis berbasis data sekunder. Hasil analisis menunjukkan bahwa kekuatan utama wilayah ini terletak pada luas kawasan pariwisata dan konservasi, sementara kelemahan utamanya adalah terbatasnya infrastruktur dasar dan pengelolaan data ruang. Peluang besar datang dari tren ekowisata dan dukungan kebijakan pemerintah, namun wilayah ini juga menghadapi ancaman serius seperti bencana alam dan konflik pemanfaatan ruang. Hasil penelitian ini merekomendasikan integrasi teknologi, peningkatan SDM, serta perbaikan tata kelola ruang sebagai langkah strategis untuk mewujudkan perencanaan ruang yang inklusif dan berkelanjutan di Kepulauan Seribu.